2008
DOI: 10.4049/jimmunol.181.11.7863
|View full text |Cite|
|
Sign up to set email alerts
|

TREM-2 Mediated Signaling Induces Antigen Uptake and Retention in Mature Myeloid Dendritic Cells

Abstract: Myeloid dendritic cells (mDC) activated with a B7-DC-specific cross-linking IgM Ab (B7-DC XAb) take up and retain Ag and interact with T cell compartments to affect a number of biologic changes that together cause strong antitumor responses and blockade of inflammatory airway disease in animal models. The molecular events mediating the initial responses in mDC remain unclear. In this study we show that B7-DC XAb caused rapid phosphorylation of the adaptor protein DAP12 and intracellular kinases Syk and phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…Therefore, we have focused on delineating the events that occur on the surface of the DCs upon binding of B7-DC XAb and to determine what membrane and intracellular molecules mediate the various DC phenotypic responses. Previously, we found that cross-linking B7-DC induced a substantial reorganization of cell surface molecules, resulting in the clustering of MHC, CD80, CD86, and CD11c molecules into a cap [3]. In this report we document that CD40 is also present within this cell surface complex on DC XAb .…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Therefore, we have focused on delineating the events that occur on the surface of the DCs upon binding of B7-DC XAb and to determine what membrane and intracellular molecules mediate the various DC phenotypic responses. Previously, we found that cross-linking B7-DC induced a substantial reorganization of cell surface molecules, resulting in the clustering of MHC, CD80, CD86, and CD11c molecules into a cap [3]. In this report we document that CD40 is also present within this cell surface complex on DC XAb .…”
Section: Discussionsupporting
confidence: 60%
“…Stimulation of DC via TREM-2 also induces a maturation response and activates ERK [25]. B7-DC XAb activates ERK, but ERK is not involved in the TREM-2 mediated response of DC to B7-DC XAb [3]. However, ERK activation was dependent on the expression of CD40 on the dendritic cells activated with B7-DCXAb.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is possible that downstream signaling by an alternative receptor engaging B7-DC may selectively lead to the upregulation of T-bet expression and the inhibition of GATA-3 expression in responder T cells. Several studies have demonstrated that cross-linking B7-DC by human anti-mouse IgM Ab results in the activation, maturation, and migration of IL-12–producing DCs (12, 48, 49). Therefore, it is also possible that the local production of IL-12 by DCs in response to reverse signaling by B7-DC is also important in generating Th1 responses in N. brasiliensis infection.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect activation of ITAM signaling by Semaphorin 6D is important not only in osteoclast differentiation but also in regulating cytokine production and antigen-presenting function of dendritic cells (which express TREM-2 and plexin A1). In addition, TREM-2–DAP12 signaling is activated in myeloid dendritic cells by PD-L2 (also called B7-DC), a molecule important in mediating effects of dendritic cells on T cell phenotype43. Thus, ITAM signaling can be triggered by various receptors and ligands important in immune responses, and in turn, ITAM signaling modulates the function of the TNFR family member RANK and myeloid cell activation and differentiation.…”
Section: Regulation Of Tnfr Family Responsesmentioning
confidence: 99%